The Need for and Path to Harmonized Life Cycle Assessment and Techno‐Economic Assessment for Carbon Dioxide Capture and Utilization. Issue 11 (11th November 2019) - Sick, Volker; Armstrong, Katy; Cooney, Gregory; Cremonese, Lorenzo; Eggleston, Alexandra; Faber, Grant; Hackett, Gregory; Kätelhön, Arne; Keoleian, Greg; Marano, John; Marriott, Joseph; McCord, Stephen; et al.
Abstract : The use of carbon dioxide as a feedstock for a broad range of products can help mitigate the effects of climate change through long‐term removal of carbon or as part of a circular carbon economy. Research on capture and conversion technologies has intensified in recent years, and the interest in deploying these technologies is growing fast. However, sound understanding of the environmental and economic impacts of these technologies is required to drive fast deployment and avoid unintended consequences. Life cycle assessments (LCAs) and techno‐economic assessments (TEAs) are useful tools to quantify environmental and economic metrics; however, these tools can be very flexible in how they are applied, with the potential to produce significantly different results depending on how the boundaries and assumptions are defined. Built on ISO standards for generic LCAs, several guidance documents have emerged recently from the Global CO2 Initiative, the National Energy Technology Laboratory, and the National Renewable Energy Laboratory that further define assessment specifications for carbon capture and utilization. Overall agreement in the approaches is noted with differences largely based on the intended use cases. However, further guidance is needed for assessments of early‐stage technologies, reporting details, and reporting for policymakers and nontechnical decision‐makers. Abstract : Carbon dioxide utilization technologies can help mitigate the effects of climate change. However, the environmental and economic impacts must be assessed to drive fast deployment and avoid unintended consequences. Life cycle assessments (LCAs) and techno‐economic assessments (TEAs) are useful but complex tools for this purpose. Herein, the efforts to develop harmonized international guidance to allow transparent and fully comparable evaluations are described.